2003
DOI: 10.1128/jb.185.3.1010-1017.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Iron-Binding Protein Dps Confers Hydrogen Peroxide Stress Resistance to Campylobacter jejuni

Abstract: whereas it did not appear to bind DNA. An isogenic dps-deficient mutant was more vulnerable to hydrogen peroxide than its parental strain, as judged by growth inhibition tests. The iron chelator Desferal restored the resistance of the Dps-deficient mutant to hydrogen peroxide, suggesting that this iron-binding protein prevented generation of hydroxyl radicals via the Fenton reaction. Dps was constitutively expressed during both exponential and stationary phase, and no induction was observed when the cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 58 publications
2
114
0
Order By: Relevance
“…Both halves were then stained with the Ferene-S stain described by Chung (Chung, 1985) and Ishikawa et al (Ishikawa et al, 2003). This consists of 1·mmol·l…”
Section: Demonstration Of Iron Binding: Electrophoresis and Blottingmentioning
confidence: 99%
“…Both halves were then stained with the Ferene-S stain described by Chung (Chung, 1985) and Ishikawa et al (Ishikawa et al, 2003). This consists of 1·mmol·l…”
Section: Demonstration Of Iron Binding: Electrophoresis and Blottingmentioning
confidence: 99%
“…H 2 O 2 ) (17)(18)(19)(20), nutrient starvation (13,15,21), and the presence of ethanol (15,16). Although Dps proteins are not essential for cell viability under normal growth conditions, it was shown that Dps deletion mutants of some bacteria are susceptible to oxidative stress (22)(23)(24), acids, bases, or UV radiation (25). Dps proteins can be induced by increasing iron concentrations in the medium (18) and may be up-regulated during iron starvation (19,26).…”
mentioning
confidence: 99%
“…The presence of Dps homologs in a wide variety of microorganisms, though with molecular divergence, suggests their importance for microorganisms' survival under many kinds of stressful environments. In most organisms Dps serves as an iron-binding protein and protects the organism from oxygen stresses (7,8,10,15). In addition, Halsey et al reported the contribution of dps to Salmonella stress resistance, survival in macrophages, and virulence in mice (7).…”
Section: Discussionmentioning
confidence: 99%